2011
DOI: 10.3837/tiis.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Stereo Image Quality Assessment Using Visual Attention and Distortion Predictors

Abstract: Several metrics have been reported in the literature to assess stereo image quality, mostly based on visual attention or human visual sensitivity based distortion prediction with the help of disparity information, which do not consider the combined aspects of human visual processing. In this paper, visual attention and depth assisted stereo image quality assessment model (VAD-SIQAM) is devised that consists of three main components, i.e., stereo attention predictor (SAP), depth variation (DV), and stereo disto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…You et al [11] investigated the capabilities of some 2D IQA algorithms for stereoscopic IQA and found that applying SSIM on stereopairs combined with a mean absolute difference to compute the disparity map distortion always yields the best performance within all possible combinations considered in the paper. Hwang and Wu [47] designed a visual attention and depth-assisted stereo image quality model, which consists of three main components: a stereo attention predictor, a depth variation predictor, and a stereo distortion predictor. Xing et al [48] proposed a perceptual quality estimator which operates based on three main factors (crosstalk level, camera baseline, and scene content) contributing to crosstalk perception in evaluating quality levels of stereoscopic presentations; the quality score of this approach is computed as the average of the SSIM-weighted disparity map.…”
Section: B Algorithms Based On Stereopair and Depth Informationmentioning
confidence: 99%
“…You et al [11] investigated the capabilities of some 2D IQA algorithms for stereoscopic IQA and found that applying SSIM on stereopairs combined with a mean absolute difference to compute the disparity map distortion always yields the best performance within all possible combinations considered in the paper. Hwang and Wu [47] designed a visual attention and depth-assisted stereo image quality model, which consists of three main components: a stereo attention predictor, a depth variation predictor, and a stereo distortion predictor. Xing et al [48] proposed a perceptual quality estimator which operates based on three main factors (crosstalk level, camera baseline, and scene content) contributing to crosstalk perception in evaluating quality levels of stereoscopic presentations; the quality score of this approach is computed as the average of the SSIM-weighted disparity map.…”
Section: B Algorithms Based On Stereopair and Depth Informationmentioning
confidence: 99%
“…Each elements of the imaging system contributes to the degradations of the system. In the past years, this subject received an increasing amount of interest [42] [43] [44] [45][46]. The main goal of image restoration is to restore the original image from the degraded scene.…”
Section: Introductionmentioning
confidence: 99%
“…For measuring the perceived quality of stereoscopic images, several metrics have been proposed by integrating 3D perceptual properties. Hwang and Wu [ 16 ] fused the impacts of visual attention, depth variation, and stereo distortion in the stereo image quality assessment. Bensalma and Larabi [ 17 ] devised a binocular energy quality metric (BEQM) by modeling the complex cells responsible for the construction of the binocular energy.…”
Section: Introductionmentioning
confidence: 99%